Pengujian Aplikasi Sistem Penjualan Barang dengan Barcode Berbasis Web Menggunakan Metode Black Box - Asep Sucipto Indra Sukma; Asep Muhammad Junaedi; Juhaendi Juhaendi; Muhammad Fauzan Sabana; Aries Saifudin (CV. Multi Kreasi Media, 2022)
Aurora Cell Repair Shop is a business unit that provides electronics repair and sales of mobile phone accessories. Today, the process of managing product sales still uses manual record-keeping systems. When totaling the total inventory sold, there are still differences in the product calculations, resulting in inaccurate total product counts. Therefore, it takes time to confirm the actual product. In this testing phase, you will design a web-based application that uses barcodes to sell products and test the application to simplify the sales process. In building this information system, sales were conducted based on an interview survey with the store owner Aurora Cell. This is a method of testing web-based information systems using the black-box method used for testing. Test results show perfect results. The system facilitates the processing of inventory control data by Aurora Cell's cashiers, enables accurate collection and data retrieval of inventory information, and facilitates decision making based on data within the system. Inventory control.